HYDROLOGICAL CONDITIONS IN THE INSHORE REGION OF KARWAR DURING 1965-1967 - Annigeri, C G (Indian Journal of Fisheries, 2011)
Studies on the hydrological conditions off Karwar were undertaken onboard one of the vessels of I.N.P. during the years 1965 to 1967. The inshoresamples collected from surface, 10 m and bottom (15-31 m), showed quite distinctdemarlcation in the distribution of physico-chemical properties. The averagemonthly values of pH fluctuated between 8.0 and 8.4. Dissolved oxygen reachedits maximum in the sub-surface layers. Saturation and supersaturation valueswere frequently observed at 10 m and 15-31 m than that at surface, indicating thezone of maximum photosynthesis below the surface waters. The distribution ofnutrient salts showed that they are concentrated at bottom